Evaluation of Free Tissue Transfer in The Reconstruction of Soft Tissue Defect in The Leg - Atmodiwirdjo, Parintosa; Hendra, Fakhrul (Lingkar Studi Bedah Plastik Foundation, 2012)
Background: There are many possible reconstructive options for reconstruction of defects in the lower limb. These include:skin grafts, local flaps, distant flaps and free flaps.Patients and Methods: We present four cases with soft tissue defects in the legs who were admitted to the Plastic and Reconstructive Surgery Division, Cipto Mangunkusumo Hospital, Jakarta, between February 2009 and February 2010. Result: In all four cases, the free anterolateral thigh (ALT) flaps have been performed for reconstruction of soft tissue defect in the upper third of the leg (3 patients) and lower third of the leg (1 patient). The cause of soft tissue defect was trauma in 3 patients and malignancy in 1 patient. All of the donor sites have similar size with the defect tissue with 15 to 20 cm in length and 10 to 15 cmin width. End-to-end microvascular anastomosis was performed in 2 cases while end-to-side anastomosis was done in the other 2 cases. Arterial thrombosis and infection were complications found in early post-operative period. Arterial thrombosis caused failure in 1 case of free ALT flap which were reconstructed further with free radial forearm flap. Summary: Free ALT flap is relatively easy to harvest once the technique of perforator flap dissection has been learnt. It has a reliable blood supply despite some anatomic variability, it is pliable and can be thinned to a significant degree without compromising blood supply, and can provide a long pedicle with large-diameter vessels.